Mediators in psychological and psychoeducational interventions for the prevention of depression and anxiety: a systematic review - Moreno-Peral, Patricia; Bellón, Juan Ángel; Huibers, Marcus J. H.; Mestre, José M.; García-López, Luís Joaquín; Taubner, Svenja; Rodríguez-Morejón, Alberto; Bolinski, Felix; Sales, Célia M. D.; Conejo-Cerón, Sonia (Clinical psychology review, 2020)
Although efforts have been undertaken to determine how psychological interventions exert their effects, research on mediators and mechanisms of change remains limited, especially in the field of prevention. We aimed to assess available evidence on mediators of psychological and psychoeducational interventions for the prevention of depression and anxiety in varied populations. A systematic review using PubMed, PsycINFO, Web of Science, Embase, OpenGrey, and the Cochrane Central Register of Controlled Trials was performed. Two independent reviewers assessed the eligibility criteria of all articles, extracted data, determined the risk of bias in randomized controlled trials, and the requirements for mediators. The outcomes were mediators of the incidence of depression or anxiety and/or the reduction of symptoms of depression or anxiety. We identified 28 nested mediator studies within randomized controlled trials involving 7442 participants. Potential cognitive, behavioral, emotional and interpersonal mediators were evaluated in different psychological and psychoeducational interventions to prevent depression and anxiety. The effects were mediated mainly by cognitive variables, which were the most commonly assessed factors. For depression, the mediator with the strongest empirical support was negative thinking in adults. Cognitive change is an important mediator in preventive psychological and psychoeducational interventions for both anxiety and depression. - Registration details - Registration number (PROSPERO): CRD42018092393.